THE EFFECT OF ASSEMBLR EDU ON THE FOURTH-GRADE STUDENTS’ VOCABULARY AT SDN LIRBOYO 2 - Fery Satria Hutama; Agung Wicaksono; Mahendra Puji Permana Aji (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2026)
English vocabulary mastery is fundamental to developing language proficiency; however, many elementary school students still experience difficulties in learning and retaining English vocabulary due to the limited use of interactive instructional media. This study aimed to investigate the effect of Assemblr Edu on the English vocabulary mastery of fourth-grade students at SDN Lirboyo 2 during the 2024/2025 academic year. A pre-experimental research design employing a one-group pretest-posttest approach was adopted. The participants consisted of 28 fourth-grade students selected through total sampling. Data were collected using vocabulary tests administered before and after the implementation of Assemblr Edu, which integrated the AR Viewer and Instant Presentation features to teach vocabulary related to Things in the Living Room and Bedroom. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test. The findings revealed that students' mean score increased from 75.36 on the pre-test to 90.36 on the post-test. The Wilcoxon Signed-Rank Test indicated a statistically significant improvement in students' vocabulary mastery (Z = -4.406, p < .001), with 25 students showing improved scores, three students maintaining the same scores, and none experiencing a decrease. These findings demonstrate that Assemblr Edu is an effective technology-enhanced learning medium for improving English vocabulary mastery among elementary school students by providing interactive, visual, and contextual learning experiences. The study suggests that integrating Augmented Reality into English vocabulary instruction can support more engaging and meaningful learning for young EFL learners.